Partisipasi Perempuan dalam Kegiatan Sosial Budaya: Studi Kasus Desa Ringinanom, Kecamatan Tempuran - Lestari, Budi Sri; Azizah, Salsabilah Nur; Lutfiana, Anifatul; Anjania, Klara; Ilahita, Ridha; Setyawan, Prayogi Yusuf (Universitas Cokroaminoto Yogyakarta, 2025)
This study focuses on women's participation in socio-cultural activities in Ringinanom Village, Tempuran District, by examining how their involvement contributes to the empowerment process. This study aims to analyze women's empowerment in the development process in Ringinanom Village using Naila Kabeer's women's empowerment framework, which includes aspects of resources, agency, and achievements. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. Research informants include village women of different age groups as well as actors involved in the village development process. Data analysis was conducted descriptively and analytically to examine the dynamics of women's involvement in the village's social and institutional spaces. The discussion shows that women in Ringinanom Village have access to social resources through involvement in community organizations and activities, although this access is not evenly distributed between women and girls. In terms of agency, women tend to be more active and bold in expressing opinions than girls, who still show limited involvement. Meanwhile, the achievements of women's involvement have not yet led to a real influence on strategic decision-making. Women's participation is still largely focused on operational and non-strategic social activities. The study's conclusions indicate that women's involvement in Ringinanom Village remains largely symbolic and does not fully reflect substantive empowerment. Therefore, women need to be fully involved, from the initial planning stages through to implementation and evaluation of development outcomes, to ensure their participation has a more meaningful impact.